Addressing the Needs of African American Male Smokers Through Community Outreach and Tailored Smoking Cessation Strategies. Issue 6 (November 2018) - Lautner, Shelby C.; Garney, Whitney R.; Harney, Idethia S.
The prevalence of adult smokers within the state of Texas population is 19.2% with 25% of those smokers being African American. Although the smoking rate of African Americans in Texas is very high, they only represent about 18% of the calls to the Texas Tobacco Quitline. To investigate this phenomenon, researchers from Texas A&M University completed a qualitative study to investigate the social norms and awareness of the Quitline among African American males. Focus groups were conducted in a rural community to determine perceptions and attitudes towards smoking among the African American population, as this was an exploratory study. The focus group participants were 71% smokers and 90% identified as African American. Data collected during the focus groups revealed information three major themes which were derived from the research question. These themes were social norms of smoking, smoking cessation, and services needed for smoking cessation. Information learned was insightful because little information exists about successful smoking cessation strategies specifically for African American male subpopulations. With this information, data can be further synthesized and outreach strategies can be further developed to help decrease the gap in health equity as it related to African American males and smoking and increase calls to the Quitline.